Transformation Of Print Media To Digital Media In Facing The Era Of Information Technology - Daud, Rosy Febriani; Wiwiek Nurkomala Dewi (PT ARRUS Intelektual Indonesia, 2024)
Over time, the development of information technology has changed the perspective of transforming print media into digital media. In this modern era, we have witnessed a significant shift from conventional publications to digital platforms like today, creating challenges and opportunities to gain new opportunities. In the past, print media has now begun to adapt to the changes that occur in the current information technology era. In facing the transformation from print media to digital media, this shift not only affects business models but also changes the way audiences search for information in the media digital. This research uses a qualitative method for the data analysis stage using literature study. In this approach, researchers collect and evaluate various literature sources such as books, articles, journals and related documents to form a solid conceptual framework for constructing verification or conclusions. The findings of this research state that the transformation of print media to digital media in the era of information technology has had a major influence on people's search for information.